2015
DOI: 10.1007/s12040-015-0606-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting, mapping and monitoring of land subsidence in Jharia Coalfield, Jharkhand, India by spaceborne differential interferometric SAR, GPS and precision levelling techniques

Abstract: The study aims at detection, mapping and monitoring of land subsidence in Jharia Coalfield, Jharkhand, India by spaceborne DInSAR, GPS and precision levelling techniques. Using multi-frequency C-and L-band DInSAR, both slowly and rapidly subsiding areas were identified and DInSAR-based subsidence maps were prepared. C-band DInSAR was found useful for detection of slowly subsiding areas whereas L-band DInSAR for rapidly subsiding and/or adverse land cover areas. Due to dynamic nature of mining and adverse land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 11 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…It has been observed that for the same test site the subsidence rate obtained from D-InSAR processing is coming very close to the PS-InSAR displacement rate. The value obtained for Jamadoba Test site using D-InSAR is coming value of 39.04 cm/yr (R. S. Chatterjee et al, 2015).…”
Section: Ps Insar Integration With D-insar Resultsmentioning
confidence: 95%
“…It has been observed that for the same test site the subsidence rate obtained from D-InSAR processing is coming very close to the PS-InSAR displacement rate. The value obtained for Jamadoba Test site using D-InSAR is coming value of 39.04 cm/yr (R. S. Chatterjee et al, 2015).…”
Section: Ps Insar Integration With D-insar Resultsmentioning
confidence: 95%
“…Thereby, unless any geophysical phenomenon causing substantial surface deformation oriented in NS direction, LOS measurements from Sentinel-1 can be assumed to consist of surface deformation in vertical and EW direction. From the field knowledge and literature survey, we do not find any phenomenon in JCF that causes substantial subsidence only in NS direction [38]. Hence, we have modified the 3D model to a 2D model by neglecting the surface deformation in NS direction.…”
Section: Decompositionmentioning
confidence: 99%
“…As an alternative, the potential of Interferometric Synthetic Aperture Radar (InSAR) was explored for coal fire mapping [38][39][40]. While overcoming the limitations of TIRbased studies and mapping geo-environmental indicators, InSAR also delivers additional advantages in coal fire mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharya et al (2012) estimated interseismic deformation along parts of Himalayan Frontal thrust using InSAR technique. Further, this technique was also used to map surface deformation associated with fluid extraction (Chatterjee et al, 2006), land mining (Chatterjee et al, 2015), landslide motion (Bhattacharya et al, 2015;Bhattacharya and Mukherjee, 2016), geomorphic changes (Majumdar, 2013) and glacier dynamics (Rao, 2011;Saraswat, et al, 2013;Satyabala, 2016). In this article we report and review the recent contributions on earthquake deformation studies from Indian researchers using the InSAR technique.…”
Section: Insar Studies For Crustal Deformation -Indian Scenariomentioning
confidence: 99%